Efektivitas Modul Untuk Meningkatkan Pengetahuan Sikap Dan Praktik Ibu Dalam Pemberian Makan Anak Stunting Di Kecamatan Kalasan - Prihartanti, Tutus Anggi; Murni, Dewi Astuti; Winda, Desy (JURNAL PENDIDIKAN KESEHATAN, 2023)
Short toddlers or commonly referred to as stunting are one of the nutritional problems experienced by toddlers in the world today. According to WHO around 22.2% of children under five in the world experience stunting and 55% of stunting toddlers come from Asia. This is possible because of improper feeding behavior. This study aims to analyze the effectiveness of the module to improve the knowledge, attitudes and practices of mothers in feeding stunting children aged 6-23 months in Kalasan District. This study is a Quasi Experiment study with pretest-post test with control group design. The population was 229 with the Simple Random Sampling method with 22 mothers having stunting children aged 6-23 months in each group. The research instrument uses modules, booklets, knowledge questionnaires, attitudes and food recall sheets. Analysis using Paired T-Test, Independent T-Test and Manova. This research has obtained Ethical Clearance from the Poltekes Ministry of Health DIY. The increase in behavior in the experimental group was greater than in the control group after the intervention was given. Knowledge with p-value 0,000, attitude with p-value 0,000, practice seen from energy intake with p-value 0,006 and protein with p-value 0,019. There is no influence of factors outside variables on increasing knowledge, attitudes and practices. Providing counseling with module media is more effective than booklets in increasing the knowledge, attitudes and practices of mothers in feeding stunting children aged 6-23 months in Kalasan District. It is hoped that the module can be used as an alternative medium for health education to improve the knowledge, attitudes and practices of mothers in feeding stunting children.